Professionalization of peace education through wiki networking and innovative teaching methods : final report. - Ware, Helen (Australian Learning and Teaching Council, 2010)
Report of a project that aimed to develop a network of peace studies educators, thereby creating a sustainable community of practice able to investigate issues of concern, needs and priorities for peace studies and its delivery within the Australasian higher education sector. The project sought to gauge the impact of these issues on effective learning outcomes within the discipline, both for those who are professionally engaged in the discipline and for those who have a more general interest. The establishment of a peacewiki created a focal hub for tertiary peace studies in Australasia. [p.1, ed]